Local-electrostatics-induced oxygen octahedral distortion in perovskite oxides and insight into the structure of Ruddlesden–Popper phases - Youngjae Hong (Nature Portfolio, 2021)
The authors observe two-dimensional shear faults in five different perovskite-type materials and detailed structures of more than 80 oxides and halides to elucidate an electrostatic origin for Jahn–Teller-type tetragonal distortion of oxygen octahedra.